Hubungan Pemberian Zat Besi (Fe) terhadap Pencegahan Anemia pada Ibu Hamil dan Kejadian Berat Badan Lahir Rendah - Aysah Aysah; Sherly Laurencia; Kurnia Nur Hasna (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Anemia in pregnant women is a significant health problem, especially in developing countries, where its prevalence can reach 43%. Anemia can increase the risk of low birth weight (LBW), which negatively affects the health of the baby. Therefore, it is important to understand the factors that influence pregnant women's adherence to taking blood supplement tablets (TTD) and its impact on maternal and infant health. Objectives: This study aimed to explore the relationship between knowledge, attitude, and family support on pregnant women's adherence to taking iron tablets, and to analyze the relationship between anemia in pregnant women and the incidence of LBW. Methods: The method used in the preparation of this journal is the literature review method. Results: The results showed that there was a significant relationship between mothers' knowledge about the importance of iron and their compliance in taking iron tablets, with a highly significant p value. Family support was also shown to play an important role in improving the adherence of pregnant women. Overall, this study emphasizes the need for appropriate interventions and continuous education on the importance of iron consumption during pregnancy to reduce the risk of anemia and LBW.